Nanoparticle sensor for label free detection of swine DNA in mixed biological samples - M. E., Ali; Uda, Hashim, Prof. Dr.; S., Mustafa; Y. B., Che Man; M. H. M., Yusop; Mohd Fazalul, Bari; Kh. N., Islam; M. F., Hasan (IOP Publishing Ltd., 2011)
Link to publisher's homepage at http://iopscience.iop.org/